2023
DOI: 10.3390/rs15061613
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Airborne Scatterometer NRCS Semicircular Sampling for Sea Wind Retrieval

Abstract: Airborne scatterometer capability depends on not only the device’s technical characteristics but also the scheme used for surface observations. Typically, a rotating-beam scatterometer uses a circular scheme for sampling normalized radar cross-sections (NRCS) at wind measurements over the sea. Here, we investigate wind retrieval using an updated semicircular scheme, providing the NRCS sampling at various combinations of incidence angles within the range 30° to 60°. The effectiveness of the wind retrieval using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In previous work, to verify a wind vector retrieval procedure in the case of a semicircular observation scheme, we performed simulations considering the right-side NRCS semicircle with azimuths from 0° to 180° presented by N = 37 azimuth sectors with a 5° width, generating 261 "measured" NRCSs and integrating them for each azimuth sector [26,27]. A Rayleigh Power (Exponential) distribution and a sea water GMF by Equations 2 and 3 with an assumption of 0.2 dB instrument noise (currently considered the upper threshold for wind scatterometers) were used.…”
Section: -Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In previous work, to verify a wind vector retrieval procedure in the case of a semicircular observation scheme, we performed simulations considering the right-side NRCS semicircle with azimuths from 0° to 180° presented by N = 37 azimuth sectors with a 5° width, generating 261 "measured" NRCSs and integrating them for each azimuth sector [26,27]. A Rayleigh Power (Exponential) distribution and a sea water GMF by Equations 2 and 3 with an assumption of 0.2 dB instrument noise (currently considered the upper threshold for wind scatterometers) were used.…”
Section: -Results and Discussionmentioning
confidence: 99%
“…Recently, we have shown that a semicircular observation scheme allows doubling the maximum altitude of sea wind retrieval compared to a circular observation scheme [26,27]. Therefore, since sea wind retrieval is an integral part of the sea water/ice discrimination procedure, a semicircular observation scheme also doubles the maximum altitude of the sea water/ice discrimination method for a high-altitude conical scanning radar.…”
Section: -3-results Summarymentioning
confidence: 99%
See 3 more Smart Citations